Village Government Policy and Sustainable Nature Tourism Development: A Case Study of Ulu Petanu Waterfall - Ni Komang Deviana (Tulisan Ilmiah Pariwisata (TULIP), 2026)
This study analyzes the implications of village government policies on environmental preservation at the Ulu Petanu Waterfall tourist attraction. Utilizing a descriptive qualitative approach, this research is framed within the Triple Bottom Line (TBL) framework Profit, People, Planet to evaluate how local regulations navigate the tension between tourism-based economic ambitions and the demands of maintaining ecosystem integrity sustainably. Data were comprehensively collected through direct field observations and in-depth interviews with two primary stakeholders: the Head of Kedisan Village as the regulator, and the management of the Village-Owned Enterprise (BUMDes) as the operational implementer in the field. The findings indicate that while village government policies have successfully facilitated digital infrastructure development and community social empowerment programs, they also carry significant ecological implications. The negative impacts identified include the transformation of the natural landscape and decreased soil stability around the waterfall area. These findings emphasize that village leadership must urgently integrate regenerative principles into local regulations to ensure Ulu Petanu remains a resilient ecological and economic asset for the village's future.